Internalisasi Nilai-Nilai Fiqih Ibadah Melalui Kegiatan Ekologi Pesantren Untuk Membentuk Generasi Berkesadaran Moral di Pondok Pesantren Annuqayah Lubangsa Guluk-Guluk Sumenep - Hanik, Umi; Khotib, Moch.; Suhardi, Andi (Pendidikan Islam Pascasarjana IAIN Jember, 2024)
ABSTRACT Environmental challenges arise from the mutual influence between humans and their environment. This study explores the integration of Fiqh Ibadah values into ecological activities at Pondok Pesantren Annuqayah Lubangsa to develop a morally conscious generation. The research focuses on three key aspects: 1) the transformation, 2) transaction, and 3) internalization of Fiqh Ibadah values through these activities. The objectives are to analyze how Fiqh Ibadah values are integrated into pesantren ecological activities to foster moral awareness. A qualitative case study approach was employed, with data collected through observation, interviews, and documentation. Data analysis followed the interactive model by Miles, Huberman, and Saldana, involving data condensation, display, and conclusion drawing. Triangulation was used to ensure validity. The findings show that the internalization of Fiqh Ibadah values has been ongoing for about a year through pesantren regulations and daily student practices. This process includes evaluations of both implementation and outcomes to measure students’ progress. The study highlights how ecological activities serve as a medium for instilling Fiqh Ibadah values, contributing to the development of a morally and environmentally conscious generation Keyword: Fiqh Ibadah Values, Pesantren Ecology, Morally Conscious Generation